Who Is Deprived? Who Feels Deprived? Labor Deprivation, Youth and Gender in Morocco - Serajuddin, Umar; Verme, Paolo (World Bank, Washington, DC, 2012)
One of the recurrent explanations of the Arab spring is that governments were disconnected from their populations and that public policies were simply not in line with people's sentiments and expectations. This paper provides a methodology to better understand how objective conditions of deprivation are translated into subjective feelings of deprivation using a strand of the recent literature on relative deprivation. The authors apply this methodology to better understand the question of gender and youth deprivation in the context of the Moroccan labor market. They find that the reference group (the people with whom people compare themselves) plays a pivotal role in understanding how feelings of labor deprivation are generated. This can explain the apparent mismatch between objective conditions and subjective feelings of deprivation related to joblessness among young men and women. The methodology can help us understand why greater discontent may be exhibited by a group of individuals who are in fact less deprived in a material sense. It can also potentially help governments design public policies that address objective conditions of deprivation, such as unemployment, with a better understanding of subjective implications.